1994
DOI: 10.1093/infdis/170.6.1508
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Production Patterns And Lymphoproliferative Responses In Volunteers Orally Immunized With Attenuated Vaccine Strains Of Salmonella Typhi

Abstract: New recombinant strains of attenuated Salmonella typhi used as live oral vaccines elicit potent immune responses. This study examined the patterns of cytokine production and proliferation to specific S. typhi antigens in subjects orally immunized with attenuated S. typhi vaccines CVD 906, CVD 908, and CVD 908 expressing the circumsporozoite protein of Plasmodium falciparum. After immunization, sensitized lymphocytes were found in subjects' blood that exhibited significantly increased proliferative responses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(134 citation statements)
references
References 26 publications
11
121
2
Order By: Relevance
“…Except for 2 of the 8 subjects in the Ty35000 study who showed meager, and probably biologically inconsequential, increases in IL-5 production in response to TypVac in post-immunization samples (i.e., in Vol#35000-5 day 28 post-vaccination levels were 5.7 pg/ml compared to a pre-vaccination level of 2.5 pg/ml, while Vol# 35000-2 showed 12.9 pg/ml at day 60 postvaccination compared to a pre-vaccination level of 3.2 pg/ml), there were no other significant increases in IL-5, IL-4 and IL-2 production after immunization with CVD 909 (Table 1). These results are consistent with previous findings using other attenuated S. Typhi strains [8,19,20,23,26] that also showed a dominance of Th1 responses (e.g., IFN-γ and TNF-α production), suggesting that these cytokines are likely to be important in S. Typhi immunity. Similar to the results with proliferative responses, no differences were observed between volunteers immunized with one or two doses of CVD 909.…”
Section: Cytokine Production In Response To S Typhi Flagella and Whosupporting
confidence: 93%
See 4 more Smart Citations
“…Except for 2 of the 8 subjects in the Ty35000 study who showed meager, and probably biologically inconsequential, increases in IL-5 production in response to TypVac in post-immunization samples (i.e., in Vol#35000-5 day 28 post-vaccination levels were 5.7 pg/ml compared to a pre-vaccination level of 2.5 pg/ml, while Vol# 35000-2 showed 12.9 pg/ml at day 60 postvaccination compared to a pre-vaccination level of 3.2 pg/ml), there were no other significant increases in IL-5, IL-4 and IL-2 production after immunization with CVD 909 (Table 1). These results are consistent with previous findings using other attenuated S. Typhi strains [8,19,20,23,26] that also showed a dominance of Th1 responses (e.g., IFN-γ and TNF-α production), suggesting that these cytokines are likely to be important in S. Typhi immunity. Similar to the results with proliferative responses, no differences were observed between volunteers immunized with one or two doses of CVD 909.…”
Section: Cytokine Production In Response To S Typhi Flagella and Whosupporting
confidence: 93%
“…Over the past decade we showed that immunization with several strains, including Ty21a (the licensed vaccine), CVD 906 (an ΔaroC ΔaroD mutant), CVD 908 (an ΔaroC ΔaroD mutant) and CVD 908htrA (an ΔaroC ΔaroD ΔhtrA mutant) resulted in the appearance in peripheral blood of sensitized lymphocytes that exhibit significantly increased proliferative responses and cytokine production, as well as classical and non-classical classI restricted CTL activity to purified S. Typhi antigens and S. Typhi-infected targets [5][6][7][17][18][19][20]23,25]. Moreover, we have shown that a single dose of CVD 909 also induced lymphoproliferative responses [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations